GENDER MAINSTREAMING; FIQH AL-NISA’ AL-MU’ASIR Telaah Pemikiran Nasr Hamid Abu Zayd dalam Kitab Dawairul Khaufi; Qiraah Fi Khitabil Mar’ah: DOI: https://doi.org/10.37850/cendekia.v12i1.86 - Muhammad Sya’roni (Cendekia, 2020)
In the discourse of religious texts and in the reality of social life, the position of women is always marginalized, inferior, and always below men. This requires a review of religious texts which have so far been considered to perpetuate this gap and can place the right position of women. Nasr Hamid Abu Zaid offers the Method of Reading the Religious Texts of the Qur'anic Contextualization. With this method, it is known that the Koran actually positions the position of women as equal to men.